2009
DOI: 10.1373/clinchem.2008.114132
|View full text |Cite
|
Sign up to set email alerts
|

A New Principle for Measurement of Cobalamin and Corrinoids, Used for Studies of Cobalamin Analogs on Serum Haptocorrin

Abstract: BACKGROUND: Transcobalamin (TC) and haptocorrin (HC) are serum corrinoid-binding proteins. We developed new methods for measurement of the corrinoids bound to HC and TC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 25 publications
(30 reference statements)
2
28
0
Order By: Relevance
“…Moreover, the present study demonstrated a strong correlation between aHC and totalHC, a result consistent with previously reported findings (19 ). It is possible that these associations may be explained by the molecular dynamics in the blood.…”
Section: Impairmentsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, the present study demonstrated a strong correlation between aHC and totalHC, a result consistent with previously reported findings (19 ). It is possible that these associations may be explained by the molecular dynamics in the blood.…”
Section: Impairmentsupporting
confidence: 93%
“…TC saturation (TCsat) was calculated as: 100 ϫ holoTC/totalTC (reference interval 2%-17%). Total corrinoids on HC (corHC) (reference interval 210 -740 pmol/L) and B 12 on HC (B 12 -HC) (reference interval 60 -400 pmol/L) were measured simultaneously with an analytical imprecision Ͻ13% (19 ). The total amount of B 12 analogs on HC (aHC) (reference interval 100 -380 pmol/L) was calculated as the difference between corHC and B 12 -HC.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…These data indicate that CN2-Cbi may be a prototype for a novel type of sGC-regulating therapeutic agent. It is unlikely that physiological concentrations of circulating cobinamides (Ͻ30 pM) or B 12 vitamins (ϳ300 pM) (Hardlei and Nexo, 2009) have any effects on sGC func- Because of high affinity to cyano groups, cobinamides are used for cyanide detoxification (Broderick et al, 2006) and doses of 800 mg/kg are deemed safe for laboratory animals (Brenner et al, 2010). Previous studies reported that nitrosyl-cobinamide functions as an NO donor (Broderick et al, 2007), increasing vasodilation and vasodilator-stimulated phosphoproteinphosphorylation, presumably through NO-dependent activation of sGC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we collected fortysix post-column fractions every 20 s (320 µl/fraction) between 9 and 25 min after injection. The samples were lyophilised and dissolved in 240 µl of 0·1 % PBS with 0·1 % bovine serum albumin (PBA) before measurement of B 12 , employing in-house haptocorrin ELISA (15,17) with a detection limit of 8 pmol/l B 12 . In brief, 100 µl (sample or calibrator) was incubated with apohaptocorrin, and excessive apo-haptocorrin was removed with B 12 -coated magnetic beads.…”
Section: Determination Of Vitamin B 12 Forms In Rat Tissuementioning
confidence: 99%